(3eLeY GdHMQjf aj RhGFO GdeYLejfs - (3Ydj Hf CHj HcQ Hf SdjeGf GdgjKej, CHh GdMSf, fhQ GdOjf, GdeUQj GdbGgQj,J (B807 (3g` s ((3GdbGgQI s)
(3ChdgG (B:s
(3GdMeO ddg GdeYjf Ydi JjSjQ GdYSjQ hHYO abO QCjJ GdeYLe GdChSW hGdeYLe GdUZjQ dGHf GdbGSe GdWHQGfi s
(3BNQgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde caGQI GdeLdS SHMGfc Gddge hHMeOc dG Edg EdG CfJ GSJZaQc hCJhH Edjc BNQ GdcJGH hGdMeO ddg hMOg s
(3HgG CKGQ WeSs
(3HgG fXGe GdJYbjHIs
(3cJHJ HNW eged GdfbW CMjGfkG s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdeLGejYs